(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
INTRODUCTION: The Solanum boldoense Dunal & A.DC, is endemic to Cuba, where it is found in forests and forest edges at low to medium elevations. It has two synonymous species, Solanum cardiophyllum Dunal and Solanum scandens Sessé & Moc. . In Cuba it is used as an ornamental because of the color of the blue flowers. In the form of a vine, the fruit is a globular berry, 1-1.2 cm in diameter, red when ripe. It is occasionally confused with the Mexican and Central American Species S. dulcamaroides Dunal, to which it is probably closely related. OBJECTIVES: For not having previous studies Phytochemistry it was decided to study trying to know the steroidal compounds of the species. MATERIALS AND METHODS. The plant was collected in the Serra da Grande Pedra, in Santiago de Cuba, by Dr. Victor Ramón Fuentes Fiallo, who in addition identified it and made the desiccant, which was deposited at the Experimental Plant of Medicinal Plants, Dr. Don. Tomás Roig, Minsap, Cuba. The plant was transferred to the Organic Chemistry laboratory of the Faculty of Chemistry, where the organs were separated, and placed to dry in the shade and then in an oven with air flow at 40-50 ºC, for 48 hours. After drying, the material was ground to a homogeneous powder. For the extraction, the decoction method was used for 4 hours, which was repeated 4 times. The extracts were concentrated in vacuum to syrup. From the column layer chromatographic study, it was possible to purify three steroidal compounds, which were soon identified through the layer chromatographic study, using isolated and identified steroid patterns from other Solanum species. RESULTS: From our phytochemical study, the isolation and identification of three steroidal compounds was obtained, such as Solasodine, Solasodieno and Diosgenina. CONCLUSIONS: Solanum boldoense Dunal & A. DC, has steroidal compounds such as Solasodine, Solasodiene and Diosgenin.